2014
DOI: 10.5664/jcsm.4096
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Sleep Disordered Breathing in Hospitalized Cardiac Patients: A Reduction in 30-Day Hospital Readmission Rates

Abstract: BRIEF SUMMARYCurrent Knowledge/Study Rationale: Sleep disordered breathing (SDB) is known to be common in patients with underlying cardiovascular disease. We hypothesized that diagnosing and initiating treatment for SDB in hospitalized cardiac patients would improve the overall management of their underlying cardiac condition. Study Impact: Our study identifi es a model of care that can increase the diagnosis and treatment of SDB in hospitalized cardiac patients. Finding a reduced 30-day cardiac readmission ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 39 publications
3
44
0
2
Order By: Relevance
“…Recognizing this condition in a timely and efficient manner may lead to fewer readmissions and ultimately reduce costs for this at-risk population. 22 The STOP questionnaire was used because of its recognized clinical validity among pre-operative surgical patients, simple format, interpretability, low cost, and ability to be self-administered. 23 Our preliminary results indicate significantly improved yield at a lower cost by combining the STOP questionnaire (high sensitivity) with overnight pulse oximetry (high specificity) testing.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing this condition in a timely and efficient manner may lead to fewer readmissions and ultimately reduce costs for this at-risk population. 22 The STOP questionnaire was used because of its recognized clinical validity among pre-operative surgical patients, simple format, interpretability, low cost, and ability to be self-administered. 23 Our preliminary results indicate significantly improved yield at a lower cost by combining the STOP questionnaire (high sensitivity) with overnight pulse oximetry (high specificity) testing.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Recent data suggest that early recognition of SDB in CHF patients and subsequent intervention can reduce hospital readmissions. 8,9 Although hospitalized patients with CHF present a unique opportunity for screening and diagnosing SDB, they are rarely screened or evaluated. This is partly due to low awareness, lack of expertise for evaluation, and major costs associated with performing traditional polysomnography (PSG) in hospitalized settings.…”
Section: Introductionmentioning
confidence: 99%
“…Small studies showed that CPAP in patients with HF and OSA reduced 30-day hospital readmission and emergency visits. 128 It also improved systolic function, blood pressure, and heart rate. [129][130][131] In long-term studies, CPAP decreased mortality and improved hospitalization-free survival in patients with HF and OSA.…”
Section: Early Treatment Of Obstructive Sleep Apnea In Cardiovascularmentioning
confidence: 99%